2004
DOI: 10.1261/rna.2150604
|View full text |Cite
|
Sign up to set email alerts
|

Packaging and reverse transcription of snRNAs by retroviruses may generate pseudogenes

Abstract: Retroviruses specifically package two copies of their RNA genome in each viral particle, along with some small cellular RNAs, including tRNAs and 7S L RNA. We show here that Rous sarcoma virus (RSV) also packages U6 snRNA at approximately one copy per virion. In addition, trace amounts of U1 and U2 snRNAs were detected in purified virus by Northern blotting. U6 snRNA comigrated with the RSV 70S genomic RNA dimer on sucrose gradients. We observed reverse transcription of U6 snRNA in an endogenous reaction in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…A recent report demonstrated that Rous sarcoma virus particles contain cellular spliceosomal RNAs, with U6 snRNA being the most abundant (22). Here, MLV Northern blots were probed for U1, U2, U4, U5, and U6 spliceosomal RNAs and for 7SK small nuclear RNA, a 330-nt-long RNA that acts as a negative regulator of the transcription factor p-TEFb (17) (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent report demonstrated that Rous sarcoma virus particles contain cellular spliceosomal RNAs, with U6 snRNA being the most abundant (22). Here, MLV Northern blots were probed for U1, U2, U4, U5, and U6 spliceosomal RNAs and for 7SK small nuclear RNA, a 330-nt-long RNA that acts as a negative regulator of the transcription factor p-TEFb (17) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Early work on the RNA content of RSV particles demonstrated that along with the dimer of viral RNA, 7S RNA (now known as 7SL or SRP RNA, the RNA component of the signal recognition particle [29]), 4S RNA, 5S rRNA, and trace amounts of 28S and 18S ribosomal RNAs were also present (9,21,36,46). Furthermore, in RSV, the packaging of cellular mRNA has been suggested (2), and a recent report showed that cellular spliceosomal RNAs, especially U6 snRNA, are also packaged (22).…”
mentioning
confidence: 99%
“…2C). Thus, although Y RNAs and vault RNA are both stoichiometric components of MLV virions (Garcia et al 2009;Eckwahl et al 2015) and U6 snRNA is present in 1 copy per RSV virion (Giles et al 2004), these ncRNAs do not appear to be major components of our HIV-1 virions.…”
Section: Sl Is the Major Host Cell Rna In Virionsmentioning
confidence: 94%
“…On vRNA binding, Gag forms a dimer or oligomer (30) that exposes the p10 NES or increases its affinity for CRM1-RanGTP, leading to export of the viral ribonucleoprotein complex through the nuclear pore. Although ψ-RNA selectively promotes Gag:CRM1 binding, considering that only two copies of vRNA are incorporated into each virion, it is possible that other RNAs in the nucleus [e.g., U6 and other small RNAs enriched in retroviral particles (31)(32)(33)(34)] might also bind Gag to stimulate nuclear export. Once in the cytoplasm, the MA and NC regions of Gag do not reassociate with importins because they are engaged in higher affinity interactions with RNA.…”
Section: Nucleic Acids Stimulate Cooperative Binding Of Gag To the Numentioning
confidence: 99%